Development of a Consumer Confidence Index for the Bangladesh Economy and Identification of Financial Risk Factors Affecting Consumer Confidence - Khan, Mohammad Saif Noman (AIUB Journal of Business and Economics, 2018)
This paper is oriented to analyze the consumer confidence level and development of a consumer confidence index. In light of data analyses it is evident that consumer confidence is low in Bangladesh measured according to both Conference Board Method and Tipp Indicator.Two methods have been used for analyzing consumer confidence, the Conference Board Method and TIPP Indicator Method. The primary findings of the research are that Bangladeshi residents are cautiously pessimistic about the current economy and slightly optimistic about the next six months, though, both indicators are in the lower region. They have also found to be optimistic about income growth and cautious in their assessment of future job opportunities.The principal risk factors that were identified by consumers are inadequacy and weakness in rules and regulations, lack of redress in case of financial losses, fraudulent activities, political risks, corruptions etc.